MAGNETIZATION FOR THE IMPROVEMENT OF SILK PRODUCING POTENTIAL IN MULTIVOLTINE MULBERRY SILKWORM (BOMBYX MORI LINN). - V. B. UPADHYAY; S. PRASAD (The Bioscan, 2010)
The magnetic field activates the physiological and developmental processes in the living beings there fore; the magnetization of silkworm cocoon has been studied to observe any possibility for the heavy production of cocoon. The experiments were conducted with the static magnetic field of 1000, 2000, 3000 and 4000 gauss. Variation in the strength of static magnetic field (p1 <0.01) and exposure duration (p2 <0.05) of cocoon significantly influenced the weight of silk gland in Bombyx mori. The weight of silk gland increased from 0.201g (control) to the maximum of 0.246g in case of 3000 gauss -72 hrs exposed cocoons. The weight of cocoon increases with the increasing exposure duration and magnetic strength up to 3000 gauss. The maximum weight of cocoon was recorded to be 1.072g in case of 3000 gauss-72 hrs exposed cocoons while it was minimum (0.812g) in 4000 gauss- 96 hrs exposed cocoons. The weight of cocoon shell increased with the increasing exposure duration of cocoons from 24 to 96 hrs in 1000, 2000 and 3000 gauss magnetic field and it was maximum (0.199g) in 3000 gauss-72 hrs exposed cocoons.